Histone Deacetylase Inhibitors in Cell Pluripotency, Differentiation, and Reprogramming. (8th March 2012) - Kretsovali, Androniki; Hadjimichael, Christiana; Charmpilas, Nikolaos
Abstract : Histone deacetylase inhibitors (HDACi) are small molecules that have important and pleiotropic effects on cell homeostasis. Under distinct developmental conditions, they can promote either self-renewal or differentiation of embryonic stem cells. In addition, they can promote directed differentiation of embryonic and tissue-specific stem cells along the neuronal, cardiomyocytic, and hepatic lineages. They have been used to facilitate embryo development following somatic cell nuclear transfer and induced pluripotent stem cell derivation by ectopic expression of pluripotency factors. In the latter method, these molecules not only increase effectiveness, but can also render the induction independent of the oncogenes c-Myc and Klf4. Here we review the molecular pathways that are involved in the functions of HDAC inhibitors on stem cell differentiation and reprogramming of somatic cells into pluripotency. Deciphering the mechanisms of HDAC inhibitor actions is very important to enable their exploitation for efficient and simple tissue regeneration therapies.